The effect of video games on teenagers' behavior and performance: A cross-sectional study in Tehran - Elham Dirandeh; Mohammad-Reza Sohrabi; Ali Dirandeh; Leyla Kaghazloo; Zahra Hajihashemi; Ramin Pouriran (Shahid Beheshti University of Medical Sciences, 2016)
Background: The novelty of the present study was to interpret the relation of the videogame usage in teenagers' behaviors and their performance in schools and distinctive environments. Methods: A total of 508 male and female teenage students were randomly selected from secondary schools of Tehran, the Capital of Iran. The designed questionnaire was completed by student's parents at the end of school year. School performance and students' behavior and pattern of using videogames were asked. Descriptive statistics, Contingency coefficient and chi-squared tests were used for data analysis. Results: According to the results, almost all the teenagers were interested in video games and 76.8% of students played video games once in a while. Female students whose mothers were older used video games more often than teenagers whose mothers were younger. Also, male students, whose mothers were housewives and had handheld devices in their rooms, were observed to spend more time playing games. The male students who spent more time playing video games showed more aggression than the others. In addition, female students who played video games quite often, showed abnormal behavior and strange mental status. Both genders showed high percentage of shouting and overeating, when they spent more time playing video games. Conclusion: Playing videogames has a significant effect on teenagers' behaviors but not on their school performance. Social determinants of health also have significant effect on playing videogames. Keywords: Adolescent; Educational Status; Students; Video Games